Anudo v. Tanzania (Afr. Ct. H.P.R.). (June 2019) - Manby, Bronwen
Abstract : The case of Anudo v. Tanzania is the first decided by the African Court on Human and Peoples' Rights that considers the right to a nationality. The judgment complements existing jurisprudence from the African Commission on Human and Peoples' Rights and the African Committee of Experts on the Rights and Welfare of the Child. The Court ruled that Tanzania had arbitrarily deprived the applicant of his nationality and then arbitrarily expelled him from the country.